Impact of the different doses of urea application on the damaging potentiality and number of live cases of Paddy caseworm, Nymphula depunctalis on popular rice cultivar at Cauvery command area: Urea doses impact on paddy caseworm in rice - jatagonda, Pandit; Vijaykumar, L; Balaji, BN; Shivanna, B; Thippaiah, M; Reddy, CN Lakshminarayana (ORYZA-An International Journal of Rice, 2025)
Nitrogen is one of the most important factors in development of herbivore populations. The application of nitrogen fertilizer in crops can normally increase herbivore feeding preference, food consumption, survival, growth, reproduction, and population density. This experiment was comprised of 10 treatments and laid out in a RCBD with 3 replications. The treatments included a standard check i.e., 100:50:50 kg/ha of N.P.K as per package of practice (POP-UASB-2021) and other treatments 10, 20, 30, 40, 50, 60, 70, 80, 90 % of excessnitrogen application above recommendation (standard check), It was observed that high doses of nitrogen i.e., RDF+90 % N of treatment recorded comparatively highest incidence (20.58 % leaf damages), nitrogen content (2.21% of N), whereas, the lowest leaf damage (7.36 %) and nitrogen content (0.97 %) observed in RDF treatment respectively. Live cases on some local cultivars were recorded and it is revealed that, the highest number of live cases (6.60 live cases) of paddy caseworm was recorded in Jaya cultivar, whereas the lowest number of live cases on BR-2655 cultivar (0.37) among the different cultivars. The present study provides aninsight into how excess nitrogen fertilizer shape paddy- caseworm interactions and the optimal regime of nitrogen fertilizer is proposed to improve the fertilizer-nitrogen use efficiency and reduce outbreak of herbivores insects.